UJI EFISIENSI PENAMBAHAN FEED SUPPLEMENT DENGAN DOSIS BERBEDA TERHADAP RETENSI PROTEIN DAN KELANGSUNGAN HIDUP UDANG VANNAMEI (Litopenaeus Vannamei) - Alfiyati Masfirotun; Endah Sri Redjeki; Sa'idah Lutfiah (Jurnal Perikanan Pantura (JPP), 2021)
The purpose of this study is; to determine the effect of feed supplement on different doses of feed can improve the survival and retention of vannamei shrimp protein. The method used is the Design Randomized (RAK), consisted of 4 treatments, 3 times repetition and 1 control. Every place of cultivation has spread vannamei shrimp seeds size 5 – 7 cm with the density of 20 tails / m2. Applying fish oil of every treatment of shrimp feed with appropriate concentration related to treatment, those are: F0 = Control (0 ml/kg), F1 = 5 ml/kg, F2 = 10 ml/kg dan F3 = 15 ml/kg. Based on the result of the research study, able to conclude that giving a dose of feed supplement to vannamei shrimp shows that real difference in the survival rate variables. The treatment of F2 (10 ml/kg feed) is the best treatment. While the variable protein retention showed no significant difference in all treatments.